Epistemologies of Mathematics Education: reflections among postgraduate students at Master's and Doctoral level - Pereira, Emanueli (2022)
This article provides a theoretical overview of Epistemologies of Mathematics Education and reflections on some epistemological conceptions of Mathematics Education for postgraduate students. Our bibliographic review evidenced a lage variety of concepts that can be explored on the subject. We have resorted to the answers of graduate students when asked about their epistemological conceptions concerning Mathematics Education under three aspects: understanding the production of knowledge in Mathematics Education; its impact and professional aspect; and comprehension of the research field of investigation. Our analysis point to the need of a better understanding and recognition of the different epistemological perspectives in Mathematics Education. In addition, we highlight the plurality and diversity of these conceptions, as well as the importance of establishing a commitment to the professional and scientific advancement of Mathematics Education.